An Unusual and Rare Case of Food-dependent Exercise-induced Anaphylaxis Caused by Ingestion of Potatoes - Elefterova-Florova Elena V.; Popova Dora N.; Andreeva Rositsa V. (Folia Medica, 2018)
Food-dependent exercise-induced anaphylaxis (FDEIA) is an unusual and under-recognized form of exercise induced anaphylaxis, which usually occurs if exercise takes place within a few hours after ingestion of sensitizing food, but in some cases may also arise if food follows the exercise. We report a case of a 31-year-old woman who presented to our Department with a history of repeated episodes of acute allergic reactions, triggered by physical activity, after consumption of various vegetables and legumes. This is the first described case of FDEIA in Bulgaria. We believe that there are many other undiagnosed cases, because for the correct recognition of this condition, it is essential to be familiar with the symptoms and combination of factors.